2021
DOI: 10.3390/ijerph182312332
|View full text |Cite
|
Sign up to set email alerts
|

Existential Therapy for Children: Impact of a Philosophy for Children Intervention on Positive and Negative Indicators of Mental Health in Elementary School Children

Abstract: Background: Philosophy for children (P4C) was initially developed in the 1970s and served as an educational program to promote critical thinking, caring, creative reasoning and inquiry in the educational environment. Quasi-experimental research on P4C, a school-based approach that aims to develop children’s capacity to think by and for themselves, has suggested it could be an interesting intervention to foster greater basic psychological need satisfaction in children in school settings. Objective: The goal of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Philosophy for children (P4C), a pedagogical approach that promotes critical thinking, caring, creative reasoning and inquiry in schools, is a good example of an intervention that can promote meaning making. Moreover, although it was not initially developed with the aim of having an impact on children's mental health, P4C has been shown to improve children's mental health (107,108). By fostering greater resiliency and self-determined motivation in children, P4C (and other similar interventions) could also promote greater engagement about the climate crisis and perhaps reduce distressing levels of eco-anxiety for some children.…”
Section: Philosophy For Children (P4c) and Existential Psychologymentioning
confidence: 99%
See 1 more Smart Citation
“…Philosophy for children (P4C), a pedagogical approach that promotes critical thinking, caring, creative reasoning and inquiry in schools, is a good example of an intervention that can promote meaning making. Moreover, although it was not initially developed with the aim of having an impact on children's mental health, P4C has been shown to improve children's mental health (107,108). By fostering greater resiliency and self-determined motivation in children, P4C (and other similar interventions) could also promote greater engagement about the climate crisis and perhaps reduce distressing levels of eco-anxiety for some children.…”
Section: Philosophy For Children (P4c) and Existential Psychologymentioning
confidence: 99%
“…This may help address existential threats that are provoked by climate change and foster meaning in life, namely through coherence with one's values (i.e., selfdetermined motivation) and overall purpose, appropriate to their developmental level (114). Furthermore, previous work on P4C and mental health brings us to conclude that when children are faced with existential questions, supporting them in reflecting and developing critical thinking skills about these questions improves their wellbeing and self-determination (107,108).…”
Section: Philosophy For Children (P4c) and Existential Psychologymentioning
confidence: 99%
“…This means that this approach can be used in tackling bullying behaviour in students. This is also proven by the results of previous research, which revealed that existential counseling could be used to overcome trauma in clients who are victims of bullying (Tambunan, 2021), reducing anxiety in the future (Sa'adah, 2020), improving the meaningfulness of the lives of people suffering from HIV-AIDS (Yulianti et al, 2020), reduces hedonic behaviour (Fitri et al, 2019), overcoming a situation of loneliness in LGBTQ+ Clients (Ratanashevorn & Brown, 2021), reducing bullying behaviour (Kartianti & Asgar, 2021), overcoming burnout syndrome (Ulrichová, 2012), reducing post-traumatic symptoms of stress disorder (Solgi & Ghazi, 2022), improves mental health (Malboeuf-Hurtubise et al, 2021), improves self-concept, social interaction and lowers anxiety (Modjo, 2021). From several previous research results, it is further strengthened that the existential therapy approach has been proven and tested in solving various client problems…”
Section: Diagram 1 Comparison Of Pretest and Posttest Datamentioning
confidence: 99%